1997
DOI: 10.1007/bf02267724
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic involvement in multiple sclerosis: a pupillometric study

Abstract: To study pupillary autonomic function in multiple sclerosis (MS), we examined 36 subjects with low disability, preserved visual acuity and no recent history (2 years) of optic neuritis or actual visual complaints. Compared to controls, MS patients showed a greater dilatator reaction with darkness and, for the light reflex, a lower amplitude and contraction rate and a greater recovery of pupillary diameter 5 s after the stimulus. Within the MS group, no difference was found comparing patients with or without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
1
35
0
2
Order By: Relevance
“…This pupillary function impairment appears to be affected early in MS. 23,24 Vasomotor symptoms were rare in this group, with only a small percentage of patients complaining about colour changes in the skin.…”
Section: Discussionmentioning
confidence: 77%
“…This pupillary function impairment appears to be affected early in MS. 23,24 Vasomotor symptoms were rare in this group, with only a small percentage of patients complaining about colour changes in the skin.…”
Section: Discussionmentioning
confidence: 77%
“…Jacobsen [6] showed that the functions are well preserved in patients with normal visual acuity. In the study by Pozzessere et al [13] pupillary abnormalities were demonstrated in 25% of the 36 MS patients with mean EDSS of 1.6. They concluded that the reduction in parasympathetic tone, together with a relative increase of sympathetic dilator tone, results from a non-specific involvement of central pathways serving the activity of the pupil.…”
Section: Discussionmentioning
confidence: 94%
“…MS is a well-known chronic inflammatory demyelinating disorder of the central nervous system and may be accompanied by clinical symptoms of autonomic dysfunction including impaired secretory functions, sexual impotence,and impaired sphincter control and pupillary dilatation [3,19]. Relapsing-remitting form of MS often causes disturbances of autonomic nervous system.In addition, frequently observed autonomic nervous system disturbances include bladder, bowel, sphincters, sexual dysfunction and sweating; cardiovascular rhythm disturbances (usually atrial fibrillation) have been observed in acute relapses of MS [4,10,21].…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic involvement may become manifest by pupillary, bowel, bladder, sweating, and sexual problems [3,19]. Cardiovascular reflexes are also known to be abnormal in MS patients [1,17,18].Abnormalities in heart rate variability and autonomic regulation in this population suggest that a significant number of MS patients show evidence of autonomic dysfunction during both baseline and exercise conditions [1,17,18,22].…”
Section: Introductionmentioning
confidence: 98%